Impact of Early Childhood Learning Experiences on Civic Tolerance and Social Integration Among Upper Basic School Students in Gusau Local Government Area, Zamfara State, Nigeria - Sule Muhammad; Binta Muhammad (Journal of Early Childhood Development and Education, 2026)
Background: Early childhood learning experiences are crucial in shaping students’ social behavior, moral values, and civic attitudes. In diverse societies such as Nigeria, early educational exposure is essential for promoting civic tolerance and social integration. However, limited empirical evidence exists regarding this relationship among upper basic school students in northern Nigeria. Objective: This study examined the impact of early childhood learning experiences on civic tolerance and social integration among upper basic school students in Gusau Local Government Area, Zamfara State, Nigeria. Guided by Vygotsky’s Sociocultural Theory, the study focused on the role of early social and educational interactions in fostering empathy, cooperation, and civic responsibility. Methods: A quantitative descriptive survey design was adopted. A sample of 384 upper basic school students was selected using stratified random sampling. Data were collected through a validated questionnaire with a reliability coefficient of 0.87. Descriptive statistics were used to answer the research questions, while Independent Samples t-test and One Way ANOVA were employed to test the hypotheses at a 0.05 level of significance. Results: The results showed that students with richer early childhood learning experiences demonstrated significantly higher levels of civic tolerance and social integration than those with limited exposure. Significant differences were observed between students with high and low early learning experiences, while ANOVA results indicated a strong association among early learning experiences, civic tolerance, and social integration. Conclusion: The study concludes that early childhood education plays a vital role in fostering civic tolerance and social integration. Enhancing early learning environments can contribute to social cohesion and the development of tolerant and civically responsible citizens. The study recommends strengthening early childhood curricula with socio-emotional and civic learning components, improving teacher training, and reinforcing education policy implementation in northern Nigeria.